تقويم الكفايات التدريسية لمدرسي المواد العلمية في المدارس الثانوية من وجهة نظر المشرفين الاختصاصيين - فاضل خلف السامرائي, عباس (Journal of College of Education, 2020)
This study aimed to Investigating Performance of Teaching Competencies by Sciences Teachers in Secondary Schools in )Salah Al_Deen( State  from the Point of View of Teacher Supervisors .   To fulfill this aim the researcher design a questionnaire of (53) item was distributed in (4) scoops (administration of class, planning, execution & evaluation), after checking a questionnaire’s veracity and constancy, the study applied on a research community of teacher supervisors which was (19), The results indicate that a low performance of teaching competencies by the sciences teachers, the total level of performance of competencies was (57.29%) which is less than the lower level in this research (60%). The results showed that there were no statistically significant differences in the responses of the research sample due to gender variable.    The researcher has obtained some recommendations & suggestions such as focus on constructive programs in the colleges of education, ensure continuous training for sciences teachers and obtain active coordination between schools & universities.